Die Arbeits- und Weiterbildungssituation junger Ärztinnen und Ärzte in Deutschland: eine zusammenfassende Analyse von Befragungsergebnissen aus sechs Fachrichtungen = Work and training of young doctors in Germany : a comprehensive analysis of survey results from six disciplines - Joachim, Stephanie Christine; Bitzinger, Diane; Arnold, Hannah; Lermann, Johannes; Oechtering, Thekla H.; Schott, Sarah; Schulte, Kevin; Raspe, Matthias (Das Gesundheitswesen, 2020)
Objective The working and training conditions of young physicians in Germany have changed over the last few years, as a result of far-reaching changes in the healthcare system. Therefore, Germany-wide surveys among young physicians of several disciplines were evaluated in a pooled analysis, in order to obtain a current interdisciplinary impression of conflicts in their daily work. Material and methods Data from web-based surveys from residents training in six disciplines were analyzed together retrospectively. One focus was a gratification crises model for the assessment of psychosocial workload. Results Data on 4041 participants were evaluated. In day-today work, young physicians were burdened with a high proportion of tasks that were not directly medical. Instruments of good subspecialty training, such as training contracts, curricula and regular feedback were associated with a lower psychosocial workload, which was generally significant among the participants. An economic influence on medical-professional decisions was subjectively clearly present among the participants. Conclusion Many young doctors find the current work and training conditions in the medical work environment unsatisfactory. This might have consequences not only for the doctors themselves, but also for the patients they care for. A healthy work environment with health professionals in good health is therefore crucial and should be in everyone's interest.
Gesehen am 18.05.2020